The Experience of "Hitting Rock Bottom" Among Recovering Alcoholics: A Phenomenological Approach - Henao Escobar, Juanita; Facultad de Psicología, Universidad de la Sabana. Colombia (Universidad Santo Tomás, Colombia, 2013)
Availing of the phenomenological method, this study aims to describe the experience of "hitting bottom" among recovering alcoholics. In-depth interviews were conducted with five men and three women who belong to the Alcoholic Anonymous community. These individuals were selected through a maximum variation sampling procedure. The results demonstrate that, due to the accumulation of critical events, in "hitting bottom" an alcoholic becomes aware of his/her existential ruin, is questioned for his/her life, feels a desire to change course, desists from the road toward self-destruction, seeks help, experiences feelings of hope and liberation, and begins a process of rebirth and transformation that leads him/her to stop drinking and therefore to a healthier life. Such an experience involves enormous suffering, precedes the process of recovery from alcoholism whereto it seems to be necessary.